Fluorescent probes for the detection of reactive oxygen species in human spermatozoa - Sara Escada-Rebelo; Francisca G Mora; Ana P Sousa; Teresa Almeida-Santos; Artur Paiva; João Ramalho-Santos (Asian Journal of Andrology, 2020)
Reactive oxygen species (ROS) production is a by-product of mitochondrial activity and is necessary for the acquisition of the capacitated state, a requirement for functional spermatozoa. However, an increase in oxidative stress, due to an abnormal production of ROS, has been shown to be related to loss of sperm function, highlighting the importance of an accurate detection of sperm ROS, given the specific nature of this cell. In this work, we tested a variety of commercially available fluorescent probes to detect ROS and reactive nitrogen species (RNS) in human sperm, to define their specificity. Using both flow cytometry (FC) and fluorescence microscopy (FM), we confirmed that MitoSOX™ Red and dihydroethidium (DHE) detect superoxide anion (as determined using antimycin A as a positive control), while DAF-2A detects reactive nitrogen species (namely, nitric oxide). For the first time, we also report that RedoxSensor™ Red CC-1, CellROX® Orange Reagent, and MitoPY1 seem to be mostly sensitive to hydrogen peroxide, but not superoxide. Furthermore, mean fluorescence intensity (and not percentage of labeled cells) is the main parameter that can be reproducibly monitored using this type of methodology.